Photocathode: Free‐Standing Bialkali Photocathodes Using Atomically Thin Substrates (Adv. Mater. Interfaces 13/2018). Issue 13 (6th July 2018) - Yamaguchi, Hisato; Liu, Fangze; DeFazio, Jeffrey; Gaowei, Mengjia; Narvaez Villarrubia, Claudia W.; Xie, Junqi; Sinsheimer, John; Strom, Derek; Pavlenko, Vitaly; Jensen, Kevin L.; Smedley, John; Mohite, Aditya D.; et al.
Abstract : Accelerator technology‐relevant photocathodes are now successfully deposited on free‐standing atomically thin substrates of graphene. This advances an ultimate goal of enhancing the lifetime of photocathodes without sacrificing the high quantum efficiency by using an atomically thin protection layer. More details can be found in the article number1800249 by Hisato Yamaguchi, Nathan A. Moody and co‐workers.